Analysis of Factors Influencing the Willingness of Taiwanese Students to Work on Mainland China: An Example of "31 Preferential Policies for Taiwan". (23rd April 2020) - Wang, Chia‐Chou; Lee, Liang‐Cheng
Abstract : In the Xi Jinping era, a key focus of the Communist Party of China (CPC), in terms of exchanges with Taiwan, is to attract young Taiwanese people to mainland China, and various policies exist to encourage their willingness to integrate. The "31 Preferential Policies for Taiwan" ("31 Measures") is an influential guiding policy for this focus. Given that the negative impact of China's "sharp power" on liberal democracy has become an international point of focus, issues such as the impact of these policies on Taiwanese youths' willingness to seek employment (or entrepreneurship) opportunities on mainland China, and factors influencing this willingness, have become major concerns for supporters of democracy globally. In order to address these questions, this study proposes four hypotheses based on theories of rational choice and political socialization. An analysis of surveys of Taiwanese students found that the mean value of students' willingness to work on mainland China was 3.22, indicating that the overall willingness of students had shifted from "neutral" towards "willing." Students perceived favor‐granting benefits and comparative benefits significantly enhanced their willingness to work on mainland China, while the life risks involved in doing so significantly reduced such willingness.